Engineering Geological Characterization of Soils and Rocks for Urban Planning: A Case Study from Wolaita Sodo Town, Southern Ethiopia - Alemu Tadese; Ephrem Getahun; Muralitharan Jothimani; Tadesse Demisie; Amanuel Ayalew (Eng)
This study was conducted to characterize and classify soils and rocks and to produce an engineering geological map that is beneficial for overall urban planning. The soils’ moisture content and specific gravity values range from 23.47% to 44.21% and 2.68 to 2.81, respectively. The activity of soils varies from 0.34 to 0.78 (inactive to normal). The shrinkage limit and shrinkage index values of soils range from 5% to 11.43% and 14.29% to 26.9%, respectively. Free swell value varies from 5 to 23% (low expansive). The unconfined compressive strength of soils ranges from 215.8 to 333.5 kPa (very stiff). According to USCS (Unified Soil Classification System), soils are classified into lean clay, lean clay with sand, fat clay with sand, and clayey silt with slight plasticity. According to BSCS (British Soil Classification SystemS), soils are classified into clay of intermediate plasticity, clay of high plasticity, and silt of intermediate plasticity. Rocks were classified into four categories based on their mass strength: very low mass strength, low mass strength, medium mass strength, and high mass strength. The RQD Rock Quality Designatione) value ranges from 47.48% to 98.25%, indicating a quality range from poor to excellent. The RMR Rock Mass Ratinge) values range from 44 to 90%, indicating that the rocks of the study area fall into three major classes: Class I (very good), Class II (good), and Class III (fair).